Los métodos de enseñanza productivos en la formación crítico-reflexiva de los estudiantes del área de ciencias sociales, de 8vo. Grado de educación general básica superior, de la unidad educativa Ismael Pérez Pazmiño, del cantón Machala, en el periodo lectivo 2013 - 2014. - Cueva Bustamante, Mayra Berenis (2014)
This research whose theoretical basis of the respective bibliographic / documentary avalizada for fieldwork in the previously selected educational institution, research was guided by clear and well defined objectives. The overall objective was : To determine the influence of productive teaching methods in training reflexive criticism of Social Sciences Area , 8th . Degree of Superior General Basic Education of the Education Unit " Ismael Pérez Pazmiño " Canton Machala , School Year 2013-2014 .